Microstructure, crystalline phase, and dielectric property analyses of TiO2 composition with ZrO2 addition - Souza, José Vitor C. [UNESP]; Castro, Pedro J. [UNESP]; Nono, Maria C. A.; Mineiro, Sergio L. (Trans Tech Publications, 2010)
For microwave applications, including mobile and satellite communications, ceramic resonators should have a high dielectric constant, low dielectric losses, and high frequency stability. In this sense, TiO2-ZrO 2 ceramics have been investigated as a function of sintering behavior, phase composition, and microstructure. The ceramics were densified reaching a value of about 86% of theoretical density at 1400°C sintering temperature. The ceramics are prepared by mixing raw materials with the following TiO2-ZrO2 weight % ratio: 100 to 0, 90 to 10, and 80 to 20, respectively. The measured dielectric constants are between 79 and 88 values, while the quality factor due to dielectric losses are between 2820 and 5170. These results point out the influence of Ti/Zr ratio on controlling the dielectric properties. © (2010) Trans Tech Publications.
Keywords: Ceramic microstructure; Ceramic resonators; Microwave dielectric properties; Phase composition; TiO2-ZrO 2; Ceramic microstructures; Crystalline phase; Dielectric constants; High dielectric constants; High-frequency stability; Low dielectric loss; Microwave applications; Quality factors; Satellite communications; Sintering behaviors; Sintering temperatures; Theoretical density; TiO; Dielectric devices; Dielectric losses; Microstructure; Optical resonators; Permittivity; Satellite communication systems; Sintering; Zirconium alloys; Ceramic materials